PENGARUH MEREK, KEPERCAYAAN DAN PENGALAMAN TERHADAP NIAT KONSUMEN DALAM MELAKUKAN TRANSAKSI SECARA ONLINE - Utama, Louis; Yuniarwati, Yuniarwati (Jurnal Ekonomi, 2016)
This study aims to prove the hypothesis that there is influence between brand orientation, trust in buying online, online buying experience in the past of the online purchase intention. The sample of this study was the students of the Faculty of Economics, University Department of Management and Accounting Tarumanagara. The analysis used multiple regression equation using the method of convenient sample selection and non-probability sampling technique. The results of this study indicate that brand orientation, trust in buying online, and online buying experience in the past has positive influence on online purchase intention either partially or simultaneously